PENGARUH MARKETING MIX TERHADAP LOYALITAS PELANGGAN - Jauhari, Tontowi; Sya'idah, Evi Husniati (Universitas Kadiri, 2018)
This study is aimed at knowing the influence of marketing mix towards customers’ loyalty. Accordingly, method used in this study is descriptive quantitative. The population of this study is the customers of bubur ayam mezem in Kediri. Moreover, the sample used in this study is 100 customers. In accordance with statistical analysis, the result of this study is as follow: (1) marketing mix that consists of product, price, and place has simultaneously a positive influence towards customers’ loyalty; (2) promotion has a negative influence towards customers’ loyalty. Thus, it can be inferred that if product, price, and place are increasing, the customers’ loyalty will be increasing as well. On the contrary, if promotion is increasing, the customers’ loyalty will be decreasing. Tujuan yang hendak dicapai melalui penelitian ini adalah untuk mengetahui pengaruh marketing mix terhadap loyalitas pelanggan. Penelitian ini menggunakan metode deskriptif kuantitatif. Populasi yang digunakan dalam penelitian ini adalah pelanggan bubur ayam mezem di Kediri dengan sampel sebanyak 100 orang pelanggan. Dari penelitian ini diperoleh hasil: (1) produk, harga dan tempat secara bersama-sama memiliki pengaruh positif; (2) promosi memiliki pengaruh negatif terhadap loyalitas pelanggan. Maka dapat ditarik kesimpulan bahwa jika produk, harga dan tempat dinaikkan maka loyalitas pelanggan juga ikut naik, tetapi jika promosi naik maka loyalitas pelanggan turun.